(untitled) (Journal of the College of Basic Education, 2022)
Social studies are of great importance, as they directly affect the developments and social conditions of societies and countries, and reveal important aspects of periods of growth, delay, or weakness for any of the social sectors, and since learning constitutes an essential and important pillar in any society, and gives pictures of the development or creation of this Society or that because of its touch and connection to the various groups of society as well as the diversity and age stage of it.